Meredith B. McGuire Lived Religion Concept of Santri Waria in Pesantren Al-Fatah Yogyakarta: An Analysis and Application - Nanda Tsani Azizah; Nurkhalis Djilfikar A Hi Daud; Yustina Priskila Patricia Kabes (Kalam Al Gazali: Education and Islamic Studies Journal, 2025)
This paper explores the lived religious experiences of transgender Muslims (santri waria) in Pesantren Al-Fatah, Yogyakarta, using Meredith B. McGuire’s concept of "lived religion" as a framework. It examines how these individuals navigate their religious commitments and gender identities within a community setting that blends traditional Islamic teachings with a progressive approach to inclusivity. The research highlights the tension between institutional religious norms and personal spirituality, revealing how santri waria adapt religious practices to align with their unique embodied experiences. By focusing on the interplay between material bodies, spirituality, and religious authority, this study underscores the need for a nuanced understanding of religion that accommodates diversity and challenges hegemonic narratives. The findings advocate for a rethinking of religious identity and hybridity, promoting inclusivity and acceptance within Islamic contexts.